Enhanced attitude tracking control of spacecraft via inner and outer loop sliding mode design - Xinxiang Fang; Ming Wen (PLoS ONE, 2025)
The significance of spacecraft in modern aerospace and technology is indisputable, with attitude control systems (ACS) playing a vital role in ensuring mission accuracy and safety. This study presents a dual-loop sliding mode variable structure control approach for spacecraft attitude regulation, leveraging integral sliding mode control (SMC) to design robust switching functions. The outer loop generates the angular velocity command ωc by tracking the desired attitude angle θ, while the inner loop ensures accurate torque control based on this command. The control architecture comprises an inner velocity loop and an outer position loop, with the inner loop deliberately designed to converge faster, ensuring overall system stability. Numerical simulations validate the proposed strategy’s effectiveness and highlight its potential for real-world aerospace applications.